2019
DOI: 10.1111/jdi.12991
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication improves glycemic control in type 2 diabetes patients with asymptomatic active Helicobacter pylori infection

Abstract: Aims/Introduction Helicobacter pylori infection is associated with insulin resistance and glycemia in non‐diabetes. However, the relationship between H. pylori infection and glycemia in diabetes remains inconclusive. Therefore, we explored the effect of H. pylori infection status and its eradication on glycemic control and antidiabetic therapy in type 2 diabetes patients. Materials and Methods A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
2
28
0
3
Order By: Relevance
“…12,13 Few studies have reported no such association. 14,15 According to this study, it was observed that H. pylori infection was commonly seen among type 2 diabetic group (79%) in comparison to non-diabetic group (21%). A significant association implied that there stands an association between H. pylori infection and diabetes.…”
Section: Discussionmentioning
confidence: 72%
“…12,13 Few studies have reported no such association. 14,15 According to this study, it was observed that H. pylori infection was commonly seen among type 2 diabetic group (79%) in comparison to non-diabetic group (21%). A significant association implied that there stands an association between H. pylori infection and diabetes.…”
Section: Discussionmentioning
confidence: 72%
“…This is consistent with the previously reported studies. [ 4 5 6 7 8 9 10 16 17 18 19 20 21 ] Most recently, a meta-analysis suggested a trend toward more frequent H. pylori infections in T2DM patients. [ 3 ] Meanwhile, the impact of H. pylori and T2DM was explored in Bener et al .…”
Section: Discussionmentioning
confidence: 99%
“…12 Interestingly, in Japan, the risk of DM decreased from 1.36 (95% CI, 1.10-1.67) to 0.92 (95% CI, 0.79-1.07) after H pylori eradication, 13 concordant with the findings that H pylori eradication decreased HbA1c levels in diabetic patients. 14…”
Section: Diabetesmentioning
confidence: 99%